A simple method for the simultaneous decoloration and deproteinization of crude levan extract from Paenibacillus polymyxa EJS-3 by macroporous resin - Liu, Jun; Luo, Jianguang; Sun, Yi; Ye, Hong; Lu, Zhaoxin; Zeng, Xiaoxiong (Bioresource technology, 2010)
A simple method for the simultaneous decoloration and deproteinization of crude levan extract from the endophytic bacterium Paenibacillus polymyxa EJS-3 was developed through static and dynamic adsorption tests of macroporous resins. S-8 resin demonstrated the highest decoloration and deproteinization ratios among various resins tested. Under optimized static adsorption conditions (pH 6.0, 35°C and adsorption time of 70min), the ratios of decoloration, deproteinization and polysaccharide recovery for S-8 resin were 76.8%, 78.9% and 69.0%, respectively. Under optimized dynamic adsorption condition (flow rate of 2BV/h, 160ml of 2.5mg/ml crude levan extract), higher ratios of decoloration, deproteinization and polysaccharide recovery for S-8 resin (84.6%, 91.7% and 81.3%, respectively) were observed. The method developed will provide a potential approach for large-scale production of levan from P.polymyxa EJS-3.